2005
DOI: 10.1016/j.tet.2005.08.090
|View full text |Cite
|
Sign up to set email alerts
|

Direct and stereoselective synthesis of β-d-mannosides using 4,6-O-benzylidene-protected mannosyl diethyl phosphite as a donor

Abstract: Leave this area blank for abstract info. Abstract-A direct and practical method for the construction of β-mannosidic linkages is described. While β-selectivities in the TMSOTfpromoted glycosidation of 2,3,4,6-tetra-O-benzyl-D-mannosyl diethyl phosphite are found to be highly dependent on the reactivity of acceptor alcohols, 2,3-di-O-benzyl-4,6-O-benzylidene-D-mannosyl diethyl phosphite reacts with a wide range of acceptor alcohols in the presence of TMSOTf in CH 2 Cl 2 at -45 °C to give β-mannosides in high yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 103 publications
1
12
0
Order By: Relevance
“…It should be noted that the loss of β‐selectivity in the absence of triflate‐based promoters has also been reported by other studies 16e. 17k, 34 A possible explanation is that when TMSOTf was used, the counter anion of the mannosyl oxocarbenium ion was the triflate anion and thus the two ions quickly coupled to generate the covalent α‐mannosyl triflate. This α‐mannosyl triflate would follow an S N 2‐like pathway and produce the β‐mannoside.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…It should be noted that the loss of β‐selectivity in the absence of triflate‐based promoters has also been reported by other studies 16e. 17k, 34 A possible explanation is that when TMSOTf was used, the counter anion of the mannosyl oxocarbenium ion was the triflate anion and thus the two ions quickly coupled to generate the covalent α‐mannosyl triflate. This α‐mannosyl triflate would follow an S N 2‐like pathway and produce the β‐mannoside.…”
Section: Resultssupporting
confidence: 68%
“…However, the improvement of β‐selectivity was less pronounced in the glycosylations of diisopropylidene acetal protected galactopyranosyl acceptor 8 (entries 4–6). A search in literature revealed that the β‐mannosylations of the galactopyranosyl acceptor 8 often result in modest β‐selectivities to other glycosyl acceptors 17k. 31 This peculiar result may be due to a mismatched interaction between the mannosyl donor 6 and galactopyranosyl acceptor 8 in the transition state leading to β‐anomer formation 32.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[26] To our delight, the desired product was isolated in 10% yield (Entry 3). [30] Product 5f should be also stored in a freezer under nitrogen. To our disappointment, elevating the reaction temperature merely led to some side rections (Entry 4).…”
Section: Cco Bn = Benzylmentioning
confidence: 99%